2013
DOI: 10.1002/jbm.b.33041
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid colloidal gels as self‐assembling elastic biomaterials

Abstract: Hyaluronic acid (HA) is a naturally occurring biodegradable polymer with a variety of applications in medicine. The use of HA as a filler or scaffold for regenerating tissues often requires improving the elastic properties of HA. This is conventionally accomplished via chemical crosslinking, which might require the generation of toxic free radicals. Although the mechanical properties of the resulting gel material can be tuned, these types of materials are static and susceptible to mechanical failure. The aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…14 HAnp were prepared using carbodiimide crosslinking chemistry using EDC with adipic acid dihydrazide (AAD) as the crosslinker. 7 Briefly, 300 mg HA (16 kDa) was dissolved in 120 mL DI water in a 500 mL round flask stirring at 300 rpm. Then, 200 mL acetone was added to the flask and stirred for 15 min.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…14 HAnp were prepared using carbodiimide crosslinking chemistry using EDC with adipic acid dihydrazide (AAD) as the crosslinker. 7 Briefly, 300 mg HA (16 kDa) was dissolved in 120 mL DI water in a 500 mL round flask stirring at 300 rpm. Then, 200 mL acetone was added to the flask and stirred for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…4, 2325 Our recent work has shown that colloidal gels with shear-thinning rheological behavior can be made out of solutions of hyaluronic acid (HA) nanoparticles. 7 These HA-based colloidal gels also have the ability to fully recover after compression to high strains and also after physically destroying and reassembling the gel, which may be attractive for applications such as for cartilage regeneration. 7 However, preliminary work demonstrated that these colloidal gels do not retain their integrity over time in culture.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In its natural state, hyaluronic acid (HA) exhibits poor biomechanical properties as a dermal fillers due to the poor viscoelasticity and the short half-life of HA when injected into normal skin [111]. To provide the ability to lift and fill wrinkles in the skin, chemical modification is required to improve its mechanical properties.…”
Section: Introductionmentioning
confidence: 99%